Establishing topic in conversation: A contrastive study of left-dislocation in English and Spanish - Hidalgo, Raquel (Círculo de Lingüística Aplicada a la Comunicación, 2023)
The syntactic construction referred in the literature as “left-dislocation” has received wide attention within the different linguistic theories. French grammars (Bally 1932) were the first to describe the construction and to coin the term, which was soon adopted by the generative model (Ross 1967). Since then, both formal and functional linguists have filled pages with their perspective on the matter, focusing, respectively and very grossly, on the syntactic properties of the construction and on its discourse pragmatic functions.